Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/s003359900731
|View full text |Cite
|
Sign up to set email alerts
|

Utility of C57BL/6J × 129/SvJae embryonic stem cells for generating chromosomal deletions: tolerance to γ radiation and microsatellite polymorphism

Abstract: We have previously reported a method for making nested deletion complexes in mice by irradiation of ES cells. The key to this technology is that F1 hybrid ES cells (called v17.2) of the genotype (BALB/cTa x 129/SvJae) retain germline colonizing ability after exposure to levels of ionizing radiation that induce chromosomal deletions. In an effort to identify other genotypes of ES cells that are suitable for this technology, the radiation sensitivity of the cell line v6.4, which is of the genotype (C57BL/6J x 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Instead, we should expand the use of hybrid ES cell lines. Hybrid ES cell lines derived, for example, from F1 intercrosses of 129 3 C57BL/6 or 129 3 BALB/c mice, retain the 129 characteristics of easy derivation and ability to be manipulated in culture while remaining competent to repopulate the mouse germline (You et al, 1998). They allow study of the effects of genetic heterogeneity observed in the human population.…”
Section: The Dilemmamentioning
confidence: 99%
“…Instead, we should expand the use of hybrid ES cell lines. Hybrid ES cell lines derived, for example, from F1 intercrosses of 129 3 C57BL/6 or 129 3 BALB/c mice, retain the 129 characteristics of easy derivation and ability to be manipulated in culture while remaining competent to repopulate the mouse germline (You et al, 1998). They allow study of the effects of genetic heterogeneity observed in the human population.…”
Section: The Dilemmamentioning
confidence: 99%
“…Mutant families carrying infertility mutations were established using chimeric male mice derived from chemically treated v6.4 ES cells of the F1 hybrid genotype C57BL/6J ϫ 129S4/SvJae (You et al, 1998). mei8 segregated as a simple recessive Mendelian trait, yielding ϳ25% affected offspring from intercrosses of heterozygotes.…”
Section: The Infertility Mutation Mei8 Causes Meiotic Prophase I Arrementioning
confidence: 99%
“…A neomycin (Neo) cassette flanked by two FRT sites and one loxP site was inserted into the third intron of the Fsp27 gene using the PL451 vector that contains this cassette. The final targeting vector was purified and electroporated into C57BL/6J x 129/ SvJae hybrid ES cells (14). After screening with G418, the correctly targeted ES clones were confirmed by Southern blotting (Fig.…”
Section: Generation Of Fsp27mentioning
confidence: 99%